The Meaning of Faqir in the Perspective of Sufism Imam Qusyairi An Naisaburi Therapeutic Study of Stress Diseases - Septa Monika; Wijaya; Heni Indrayani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Faqir is generally a word used to describe the state of society, where people are unable to meet their daily needs. Thus, the word faqir can be interpreted as a general understanding of a person or a society that cannot improve its standard of living because it cannot meet the needs of resources in its life. Stress is the body's reaction or response to psychological stressors (mental stress or life stress). Stress is a person's non-specific response to a need that exists in him. People who experience stress may behave differently than those who don't. This study aims to find out how faqir according to the perspective of Imam Al Qusyairi An Naisaburi in the book Risalah Qusyairiyah and find out how the meaning of faqir can be a therapy for stress diseases. This research is a qualitative research that focuses on literature studies. In this study, data is sourced from several sources such as in the book "Risalah Qusyairiyah Sumber Studi Ilmu Tasawuf" by Imam Qusyairyah and other sources Data obtained from sources other than the original include information data or research data such as books, journals, or documents related to research. The results of the research show that faqiran according to Imam Al-Qusyairi Be patient with fakiran, thank Allah for his efforts, preserve his religion, hide his fakira. So, when faqiran occurs, faqir according to the teachings of Sufism can cure it. Knowing the reasons and teachings of Sufism can give birth to positive values that can be used to overcome stress, namely by praying, dhikr, and reading the Qur'an. The conclusion of this study is that when a person experiences stress caused by faqir according to the community, it can be treated in the way used by faqir people in Sufism who practice the teachings of Sufism. This research is very much expected so that this faqiran will not only be a theoretical reference but also be carried out in daily life such as increasing efforts to be grateful and patient.